The Mapping of Honorific Balinese Address Terms Translated into English (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
The aim of this article is to find the mapping of Balinese address terms and its translation into English in a Folktale entitled I Juragan Anom. The mapping is used to categories and make clear the major conceptual of the address term are used in folktale I Juragan Anom. Based on the simple analysis, the mapping of Balinese address terms can be categories into three, there are: 1) Balinese address term sub-type indicating honorific: caste system; 2) Balinese address term sub-type personal name system; and 3) Balinese address term sub-type kinship.
Keywords: Mapping; Translation; Equivalent